2007
DOI: 10.1063/1.2720074
|View full text |Cite
|
Sign up to set email alerts
|

Andreev reflection study of the new magnetic superconductor Mo3Sb7: evidence of gap anisotropy

Abstract: Point-contact (PC) Andreev-reflection experiments on the new paramagnetic superconductor Mo3Sb7 are reported for which we have observed strong distinctions in the PC spectra measured for different contact axis orientations. Analysis of the PC spectra in the framework of the Blonder–Tinkham–Klapwijk theory has shown that the gap parameter Δ is strongly anisotropic, varying over a very wide range depending on the contact orientation: the maximum Δmax can exceed the minimum Δmin by at least 40 times. For these an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…So, the highest D is observed in the contacts oriented along the crystallographic directions where the gap function has a maximum. In the other so-called nodal directions with zero or close-to-zero gap function the spectra reveal the many times lower D. As before [4], we believe that the behavior of D for the lobe directions (i.e., corresponding to the maxima of gap function) with a change of temperature or magnetic field is roughly similar to that observed in conventional s-type superconductors with an isotropic gap function. Indeed, the experimental dependences D( ) T (Fig.…”
Section: (Solid Lines)supporting
confidence: 60%
See 3 more Smart Citations
“…So, the highest D is observed in the contacts oriented along the crystallographic directions where the gap function has a maximum. In the other so-called nodal directions with zero or close-to-zero gap function the spectra reveal the many times lower D. As before [4], we believe that the behavior of D for the lobe directions (i.e., corresponding to the maxima of gap function) with a change of temperature or magnetic field is roughly similar to that observed in conventional s-type superconductors with an isotropic gap function. Indeed, the experimental dependences D( ) T (Fig.…”
Section: (Solid Lines)supporting
confidence: 60%
“…A similar situation occured while measuring the temperature dependence of the order parameter of Mo Sb 3 7 in [4], where it was assumed that this superconductor has anisotropic symmetry of pairing, e.g., of the d-or sg-type. So, the highest D is observed in the contacts oriented along the crystallographic directions where the gap function has a maximum.…”
Section: (Solid Lines)mentioning
confidence: 99%
See 2 more Smart Citations
“…specific heat, NMR or µSR) to reveal the gap symmetry under pressure should shed some light on the pairing symmetry. Especially, that Andreev reflexion studies [53,54] in Mo 3 Sb 7 even at ambient pressure suggested non-BCS strong gap anisotropy, with possible s+g gap symmetry.…”
Section: Magnetism and Relativistic Effectsmentioning
confidence: 99%